2013
DOI: 10.1002/j.2055-2335.2013.tb00255.x
|View full text |Cite
|
Sign up to set email alerts
|

Anticholinergic Burden Assessed Using General Practice Electronic Records

Abstract: Aim To determine the anticholinergic burden (ACB) of an Australian primary care population. Method A cross‐sectional study was undertaken of medication data from 11 general practices. Participants were active patients aged 65 years and over seen at least 3 times in the last 2 years (n = 4853). The ACB score was calculated based on a UK peer‐reviewed scoring system (Fox) and a modified scale (Fox‐plus) that included medications not present in the Fox scale. The main outcome measure was total ACB from prescribed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Use of anticholinergic medications by elderly Australians is common. In a recent study of 4,853 individuals in general practice aged 65 and older, more than half were dispensed at least one medication with anticholinergic properties . Eight percent had a total anticholinergic burden score of 4 or more, which indicates use of at least two moderately anticholinergic agents or one mild anticholinergic and one highly anticholinergic agent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Use of anticholinergic medications by elderly Australians is common. In a recent study of 4,853 individuals in general practice aged 65 and older, more than half were dispensed at least one medication with anticholinergic properties . Eight percent had a total anticholinergic burden score of 4 or more, which indicates use of at least two moderately anticholinergic agents or one mild anticholinergic and one highly anticholinergic agent.…”
Section: Discussionmentioning
confidence: 99%
“…Eight percent had a total anticholinergic burden score of 4 or more, which indicates use of at least two moderately anticholinergic agents or one mild anticholinergic and one highly anticholinergic agent. Amitriptyline, oxybutynin, and paroxetine were the most frequently used anticholinergic medications in this study and were the most frequently dispensed anticholinergic medications in the current study. International studies have shown prevalence of use of anticholinergics of up to 90% in elderly adults .…”
Section: Discussionmentioning
confidence: 99%
“…This pilot study was designed to measure the changes in patients’ self‐management of their chronic disease before and after a clinical intervention delivered by community pharmacists in nine community pharmacies in rural New South Wales. Eighty‐six patients were enrolled and received, with their prescription repeats, medication reviews, education and PoC monitoring to provide them with immediate feedback on how their self‐management skills were affecting their disease progression . The study was minimally invasive (finger pricks) and did not involve any active medication administration.…”
Section: Design and Methodsmentioning
confidence: 99%
“…Eighty-six patients were enrolled and received, with their prescription repeats, medication reviews, education and PoC monitoring to provide them with immediate feedback on how their self-management skills were affecting their disease progression. [8][9][10] The study was minimally invasive (finger pricks) and did not involve any active medication administration. It was based upon finding out what the patient had been told, and reinforcing those messages.…”
Section: Design and Methodsmentioning
confidence: 99%
“…The medical risk factors that patients were screened for included: heart failure, chronic obstructive pulmonary disease (COPD), cerebrovascular accident (CVA) or transient ischaemic attack (TIA), epilepsy, dementia, Parkinson's disease, chronic inflammatory conditions such as rheumatoid arthritis, smoking history, excessive alcohol consumption, and body mass index (BMI) above 30 or below 20 as recorded in medical histories by medical, nursing, pharmacy and allied health staff [16,17] . Medication related risk factors that were screened for included: PPIs, antidepressants, antipsychotics, antihypertensives, loop diuretics (frusemide), anticholinergic medications, antiepileptics, thyroxine, aromatase inhibitors, gonadotrophin releasing hormone receptor agonists, androgen antagonists and warfarin [2][3][4][5][6][7][8]17,18] . As part of this post-hoc analysis the use of the FRAT was reviewed in relation to the completion of the medications risk subsection for all patients screened for the primary study, with exception of paediatric (< 18 years of age) and non-minimal-trauma admissions (see Figure 1).…”
Section: Methodsmentioning
confidence: 99%